Direct Effects, Compensation, and Recovery in Female Fathead Minnows Exposed to a Model Aromatase Inhibitor - Villeneuve, Daniel L. (National Institute of Environmental Health Sciences, 2009)
BACKGROUND: Several chemicals in the environment have the potential to inhibit aromatase, an enzyme critical to estrogen synthesis. OBJECTIVES: The objective of this study was to provide a detailed characterization of molecular and biochemical responses of female fathead minnows to a model aromatase inhibitor, fadrozole (FAD). METHODS: Fish were exposed via water to 0, 3, or 30 μg FAD/L for 8 days and then held in clean water for 8 days, with samples collected at four time points during each 8-day period. We quantified ex vivo steroid production, plasma steroids, and plasma vitellogenin (Vtg) concentrations and analyzed relative transcript abundance of 10 key regulatory genes in ovaries and 3 in pituitary tissue by real-time polymerase chain reaction. RESULTS: Ex vivo 17β-estradiol (E(2)) production and plasma E(2) and Vtg concentrations were significantly reduced after a single day of exposure to 3 μg or 30 μg FAD/L. However, plasma E(2) concentrations recovered by the eighth day of exposure in the 3-μg/L group and within 1 day of cessation of exposure in the 30-μg/L group, indicating concentration- and time-dependent physiologic compensation and recovery. Concentration-dependent increases in transcripts coding for aromatase (A isoform), cytochrome P450 side-chain cleavage, steroidogenic acute regulatory protein, and follicle-stimulating hormone receptor all coincided with increased E(2) production and recovery of plasma E(2) concentrations. CONCLUSIONS: Results of this research highlight the need to consider compensation/adaptation and recovery when developing and interpreting short-term bioassays or biomarkers or when trying to predict the effects of chemical exposures based on mode of action.